Social and Political Consequences of Reza Shah’s Acquisition - Mirdar, Morteza; Pourafarin, Foulad (Journal of History Culture and Art Research, 2017)
In this research, the effects and social and political consequences of the acquisition of land and property by Reza Khan have been addressed. The importance of the issue was due to the small amount of ownership of property and land, and consequently the change in the social and political relations of previous landowners and the replacement of Reza Khan’s trusted individuals. The main issue of this research is the explanation of some social and political events in the field of land and property acquisition. In this regard, the role of taking possession of property in advancing Reza Khan’s autocratic thoughts on the diminution of religion in social life, as well as the weakening of the power of the constitutional and opposition leaders of Reza Khan has been explained. The result of this study was the wide-ranging consequences of the acquisition of land and property in the social form of people’s lives and the transformation of the social classes on the basis of Reza Khan’s ambitious policies. This form of appropriation has changed the course of government and parliament besides it came to the end of a decade that led to the power and influence of the politician in favor of Reza Khan.